2021
DOI: 10.3390/life11010071
|View full text |Cite
|
Sign up to set email alerts
|

Smart Nanoformulation Based on Polymeric Magnetic Nanoparticles and Vincristine Drug: A Novel Therapy for Apoptotic Gene Expression in Tumors

Abstract: Background: Advanced nanobiotechnology provides safe and efficient drug delivery systems to deliver chemotherapy that targets cancer cells efficiently. Methods: A polymeric-magnetic nanocarrier was composed of a dextran (DEX) shell, a superparamagnetic iron oxide (SPION) core and was conjugated with folate (FA) to carry the anticancer drug vincristine (VNC) in Tera-1 testicular tumor cells. The molecular mechanisms by which apoptosis was induced were analyzed using flow cytometry and qPCR, which exhibited anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 24 publications
(21 reference statements)
1
17
0
Order By: Relevance
“…Studies of nanosystems specifically aimed at TC are rare – perhaps due to its relatively low incidence – however, one such study by Al-Musawi et al (2021) , covalently attached the anticancer agent vincristine to a SPION and encased this entity in dextran with surface folic acid to develop a targeted and directable NP. These NPs demonstrated a 10-fold increase in toxicity compared to the free drug when applied to Tera-1 testicular tumor cells in vitro ( Al-Musawi et al, 2021 ).…”
Section: Applications Of Nanoparticles In Male Reproductive Health Medicine and Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of nanosystems specifically aimed at TC are rare – perhaps due to its relatively low incidence – however, one such study by Al-Musawi et al (2021) , covalently attached the anticancer agent vincristine to a SPION and encased this entity in dextran with surface folic acid to develop a targeted and directable NP. These NPs demonstrated a 10-fold increase in toxicity compared to the free drug when applied to Tera-1 testicular tumor cells in vitro ( Al-Musawi et al, 2021 ).…”
Section: Applications Of Nanoparticles In Male Reproductive Health Medicine and Researchmentioning
confidence: 99%
“…Studies of nanosystems specifically aimed at TC are rare – perhaps due to its relatively low incidence – however, one such study by Al-Musawi et al (2021) , covalently attached the anticancer agent vincristine to a SPION and encased this entity in dextran with surface folic acid to develop a targeted and directable NP. These NPs demonstrated a 10-fold increase in toxicity compared to the free drug when applied to Tera-1 testicular tumor cells in vitro ( Al-Musawi et al, 2021 ). Attention has also increasingly focused on the longer-term treatment sequelae as up to 60% of survivors of TC face the aforementioned consequences of lowered testosterone levels corresponding to the cumulative dose of cisplatin ( Poniatowska et al, 2020 ).…”
Section: Applications Of Nanoparticles In Male Reproductive Health Medicine and Researchmentioning
confidence: 99%
“…Figure (2-b) showed the FA-CU-CS-Fe@Au NPs synthesized with an average size of 212.8 nm. To investigate the ability of the gold shell to keep the Fe core from, oxidation [28]. 4) presented for 96 h releases CU from (FA-CU-CS-Fe@Au NPs) and the result shows that the release time is faster at pH (5.4), when compared with pH (7.4).…”
Section: Uv-visible Absorption Spectrummentioning
confidence: 99%
“…The significant interest of nanomaterial research and development, particularly NPs, is due to their attractive characteristics, revealed by their small size, unusual high surface area activity offering excellent catalytic, optical, and electrical properties [8][9][10]. Therefore, Metallic NPs have been active in comprehensive research, methods, and advanced micro-and nanotechnology applications [1,[11][12][13][14][15][16]. Due to their unique physicochemical properties in biological applications, metal oxide NPs like iron oxide NPs (Fe3O4), manganese oxide NPs (MgO), titanium dioxide NPs (TiO2), zinc oxide NPs (ZnO).…”
Section: Introductionmentioning
confidence: 99%